Reference values of osteocalcin and procollagen type I N-propeptide plasma levels in a healthy Central European population aged 0-18 years - Bayer, M (Osteoporosis international, 2014)
UNLABELLED: The aim of this study was to assess the relationships between both a marker of bone formation and a marker of bone turnover and age, sex, and pubertal stage in a group (n = 439) of healthy children and adolescents. These reference data should be instrumental in interpretation of results. INTRODUCTION: The skeletal system has high metabolic activity. In children, bone markers may be useful in diagnostics and treatment management of skeletal diseases but there could be difficulties with interpretation of results. Compared with adults, children have elevated bone marker levels due to high skeletal growth velocity and rapid bone turnover. Thus, valid age- and sex-specific reference data should be obtained for each pediatric population living in a particular climate and with a similar lifestyle. The aim of this study was to assess the relationships between both a marker of bone formation (procollagen type I N-terminal propeptide [PINP]) and a marker of bone turnover (osteocalcin [OC]) and age, sex, and pubertal stage in a group of healthy children and adolescents. METHODS: Four hundred thirty-nine healthy Caucasian children participated. Their height, weight, and pubertal stage were recorded. Fasting PINP and OC were measured using a morning blood sample. RESULTS: The highest levels of PINP were observed during the first year of life. There is no OC postnatal peak, but levels are higher than the adult reference interval throughout childhood. OC peaks with the pubertal growth spurt at second-third Tanner stage of breast development in girls and at second-third Tanner stage of genital development in boys. PINP peaks during second-third Tanner stage of breast development in girls and at third Tanner stage of genital development in boys. CONCLUSION: This study provides reference data for OC and PINP in healthy Caucasian children from a Central European population.
Keywords: Procollagen; Infant; Anthropometry; dítě; biologické markery; předškolní dítě; novorozenec; puberta; Biomarkers; Aging; Adolescent; lidé; Infant, Newborn; osteokalcin; Osteocalcin; antropometrie; referenční hodnoty; Sex Characteristics; peptidové fragmenty; Peptide Fragments; kojenec; Reference Values; Child, Preschool; pohlavní dimorfismus; stárnutí; Child; Puberty; mladiství; prokolagen; Humans